Implementasi Teknik Relaksasi Nafas Dalam Pada Pasien Dispepsia Dengan Masalah Gangguan Rasa Nyeri - Desiathul Bafaraz, Hasril; Rouf, Abdul; Amelinda Windiani, Nosa; Shintia Devi, Putri (MEJORA Medical Journal Awatara, 2024)
Basic human needs are elements needed by every human being to maintain life and health, one of which is the need to feel safe and comfortable. The need for security or safety is a need to protect oneself from physical danger. Security, often defined as a state of being free from physical and psychological harm, is a basic human need that must be met. Security is a physiological need where a person can feel free from discomfort. The research aims to provide nursing care to improve the client's health status. The research method used is a descriptive method with a case study approach. The results include the process of assessment, diagnosis, intervention, implementation, and evaluation. After providing nursing care to the client, Mrs. W obtained the results of changes in health status which improved including no pain, no grimaces, the client looked calm and the client was allowed to go home. Implementation of nursing care for patients with disorders in fulfilling basic needs, safe and comfortable for clients, Mrs. W between theory and case is appropriate. This can be proven in the application of theory to clients